Identification, serotyping and determination of the sensitivity profile of Salmonella enterica isolated from cloacae of red-eared slider turtles (Trachemys sp) in captivity, Peru - Meza R., Dante (2020)
The aim of this study was to identify, serotype and determine the sensitivity profile of Salmonella enterica strains isolated from red-eared slider turtles (Trachemys sp) from two breeding centres in Lima, Peru, through cloacal swabs. The samples were isolated using tetrathionate enrichment broth, specific media such as Salmonella-Shigella agar and xylose lysine deoxycholate agar. The identification was made through biochemical tests. Serotyping through the recognition of somatic (O) and flagellar (H) antigens of the Kauffmann-White system, and the determination of sensitivity using the Kirby Bauer diffusion disk test. The results showed that 6.1% (4/66) of Salmonella enterica isolates were obtained, identifying the serotypes Salmonella Saintpaul and Salmonella Infantis. Antibacterial sensitivity tests indicated differences between strains, showing 100% sensitivity against nalidixic acid, norfloxacin and enrofloxacin and less for streptomycin, sulfamethoxazole + trimethoprim, chloramphenicol and amoxicillin + clavulanic acid. The results show the potential risk to public health involved in raising these turtles as potential pets.